Out of the Mouths of Babes: Developmental Differences in Young Children's Microaggressions and Relations with Parent-Child Discussions. - Zhang, Xian.; Cinney, Alexandria.; DeBenedetto, Anthony M.; Nealon-Shapiro, Cecelia.; Shin, Hae Ram.; Zhang, Emily.; Pinderhughes, Ellen E. (Tufts University. Tisch Library., 2016)
Throughout their development, transracial adoptees (TRAs) must navigate visible differences from their adoptive family, which frequently prompt public comment (Wegar, 2000) Even in the absence of family, TRAs experience questions and comments from peers about their difference (Vashchenko et al, 2012) Whether from strangers or peers, well-meaning or intentional, these comments may reflect microaggressions—daily verbal, behavioral or environmental messages, intentional or unintentional that communicate hostile or negative slights and insults (Sue et al, 2007) With ongoing exposure to racial or adoption microaggressions (Baden, 2016), young children may internalize messages that they have heard, and repeat the themes without full awareness of the impact of the messages. Yet, as children grow and become more cognitively sophisticated, they are better able to understand negative messages they hear and may refrain from conveying microaggressions. Little is known about whether there are developmental differences in microaggressions that children convey. As encouraged by adoption professionals, parents may engage in discussions with TRAs in order to promote children's understanding of their adoptive and racial status and identity development. These discussions, a component of adoption socialization (AS) and cultural socialization (CS), may enhance identity and inoculate children against internalization of microaggressions. Hence, TRAs who have these discussions may convey fewer microaggressions. Parents may have other discussions with TRAs in order to empower them to deal with stigma and microaggressions they will face (preparation for bias; PfB; Hughes et al., 2006) Nothing is known about these three types of parent-child discussions and their relations with microaggressions conveyed by TRAs. This exploratory study will examine: 1) what types of adoption and racial microaggressions are conveyed by young children?; 2) are there developmental differences in the microaggressions conveyed?; and 3) to what extent are parent-child AS, CS or PfB discussions related to the number of microaggressions conveyed by children? Forty parents and their children ages 5-10 adopted from China comprise the sample. Using a qualitative coding procedure, committed (or conveyed) microaggressions were coded when children's discourse contained bias. Empowering discussions were coded when in response to microaggressions parents helped children develop coping strategies or provided information/explanations about biases. Parent-child discussions about AS and CS were coded from parent interviews, using a three-level coding system (often, occasionally, rarely/never) to code the frequency of race and adoption discussions. Preliminary analyses of 18 families showed: children conveyed 1 to 6 microaggressions (μ=3) Parent-child empowering discussions ranged from 0 to 4 (μ=1) Parent-child discussions about race ranged from 0-2 (μ=1); discussions about adoption ranged from 0-2 (μ=1.6) Age was moderately related (trend) to the number of child-conveyed microaggressions (r= -.41): older children conveyed fewer microaggresions. Parent-child empowering discussions were moderately correlated with children's microaggressions (r= -.35): children who had more empowering discussions conveyed fewer microaggressions. Parent-child discussions about AS (-.19) and CS (.04) showed modest or no relation to children's microaggressions, respectively. Further analyses with the full sample of 40 will examine these relations and whether parent-child discussions moderate possible age differences.